Hormonal Control of Haemostasis During Hypoglycaemia in Diabetes Mellitus - Grant, P J; Stickland, M H; Wiles, P G; Davies, J A; Wales, J K; Prentice, C R M (Thrombosis and Haemostasis, 1987)
Factor VIII (FVIII) and plasminogen activator activity (PAA) rise during hypoglycaemia, and this might contribute to the vascular complications of diabetes. Similar changes in haemostasis accompany raised plasma levels of vasopressin (aVP) and adrenaline. To investigate the effects of these hormones on haemostasis during hypoglycaemia and the role of plasma insulin concentrations, eight insulin-dependent diabetic patients underwent controlled hypoglycaemia for 20 min and 13 diabetic patients were investigated during hyperinsulinaemia with blood glucose maintained at 8.0 mmol/1. During hypoglycaemia, insulin levels increased to median values of 114 mU/1, aVP rose from 0.5 to 4.4 (p <0.005) pg/ml and adrenaline from 0.4 to 4.4 nmol/l (p <0.005). FVIII coagulant activity (FVIII :C) rose from 0.75 to 1.09 iU/ml (p <0.01) and the ristocetin co-factor (FVIIIR:Co) and von Willebrand factor antigen (vWF:Ag) showed similar responses. PAA increased from 156 to 745 units (p <0.005). During hyperinsulinaemia, insulin rose following infusion from 24 to 52 and 118 mU/l, maintained for an hour at each level. Despite this, plasma aVP, FVIII :C, FVIIIR:Co, vWF:Ag and PAA remained unchanged. This study indicates that the marked changes in FVIII, vWF and PAA concentrations which accompany hypoglycaemia depend on low blood glucose and not raised plasma insulin. The response in probably mediated by increases in adrenaline and aVP, which are part of the physiological response to hypoglycaemia.
Keywords: Hypoglycaemia; Insulin; Vasopressin; Adrenaline; Factor VIII; Plasminogen activator; Insulin-dependent diabetes